1994
DOI: 10.1210/jcem.79.1.8027239
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol- and progesterone-related increases in the renin-aldosterone system: studies during ovarian stimulation and early pregnancy.

Abstract: To investigate the degree to which endogenous increases in estradiol (E2) and progesterone (P4) are associated with changes in the renin system, we studied eight patients undergoing ovarian stimulation for in vitro fertilization (FSH/human menopausal gonadotropin or clomiphene citrate for 5-11 days, followed by hCG). Three conceived and were followed for up to 62 days after hCG treatment. The others were followed until the end of the luteal phase. During the follicular phase, E2 increased 10-fold, PRA increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 12 publications
1
41
0
1
Order By: Relevance
“…In our study, the blood sampling in sitting position after being ambulatory for hours might further enhance the difference. It has been reported that sex hormone might be involved in high PRA [25,26]. Smoking is thought to be an inducer of renin secretion by increasing sympathetic activity.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the blood sampling in sitting position after being ambulatory for hours might further enhance the difference. It has been reported that sex hormone might be involved in high PRA [25,26]. Smoking is thought to be an inducer of renin secretion by increasing sympathetic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Hence many diabetic patients are treated with ACE inhibitors or Ang II receptor antagonists for hypertension or as part of a renal protection strategy. It has became clear that oestrogen can influence RAS [41][42][43][44][45][46][47] and that this effect is mediated by down-regulating renin, ACE and Ang II receptor expression [48]. An interesting review has reported that gender and sex hormones affect the components of RAS by multifarious mechanisms [9].…”
Section: Figure 3 Captopril and Pravastatin Augment Insulin Secretionmentioning
confidence: 99%
“…Sealey et al [4] studied women undergoing ovarian stimulation for fertilization and found that PRA and urinary excretion of aldosterone were significantly increased during the luteal phase of the menstrual cycle, when plasma estrogen levels are highest, compared with other phases. Furthermore, a significant positive correlation existed between levels of these RAS components and estrogen.…”
Section: Gender Differences In Renin-angiotensin System Functionmentioning
confidence: 99%
“…Given the key role of the renin-angiotensin system (RAS) in the pathogenesis of hypertension, cardiovascular disease, and chronic renal disease, gender differences in RAS function have received increasing attention. Studies of the impact of gender on the RAS have provided conflicting results, with groups suggesting that the system is activated [3,4] or suppressed [5] in women compared with men. Most studies in humans examining the relationship between gender, estrogen status, and the RAS have been limited by reliance on baseline measurements of components of the system.…”
Section: Introductionmentioning
confidence: 99%